Investigation of the effects of silicone oil coating and hot air drying on the optical and physical properties of heat-set web offset printing papers - Tutak, Dogan; Aydemir, Cem; Akgul, Ahmet (Journal of Graphic Engineering and Design, 2018)
Heat-set web offset printing is a printing system that ink dries quickly with hot air. It is one of the preferred printing techniques with high speed printing process and print quality. Web offset printing machines produce approximately 60,000-70,000 iph (impressions per hour). Because of this speed, printing paper should be very durable during the printing process. In this study, three different (70 g/m2 high-grade, 70 g/m2 glossy coated and 90 g/m2 matte coated) roll papers were used. All these papers were printed with Goss M600 web offset printing machine. Three kinds of samples (non-oven - non-silicone, ovened – non-silicone and ovened - siliconed) were taken from every paper type and optical and physical tests were applied to these samples. It was determined that heat-set web offset printing papers showed different responses to temperature and silicone oil coating in the direction of the obtained results. All printed papers were compared only to their own kind, not the other type of papers.